2022
DOI: 10.1080/14779072.2022.2066522
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis following COVID-19 vaccination: incidence, mechanisms, and clinical considerations

Abstract: Introduction Vaccines have demonstrated protection against the morbidity and mortality of COVID-19, but concerns regarding the rare side effect of acute myocarditis have stymied immunization efforts. This review aims to describe the incidence and theorized mechanisms of COVID vaccine-associated myocarditis and review relevant principles for management of vaccine-associated myocarditis Areas covered Epidemiologic studies of myocarditis after COVID vaccination are reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 117 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…The potential mechanism of mRNA COVID-19 vaccine-induced myocarditis remains unknown. It has been suggested that excessive innate immune activation by both lipid nanoparticle and RNA components of COVID-19 vaccines can cause myocarditis [24,25]. Endosomal toll-like receptor (TLR) TLR3, TLR7, and TLR8 in immune cells and RIG-I and MDA5 in nonimmune cells act as a natural defense against foreign RNA but can crossreact with in vitro transcribed (IVT) RNA [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mechanism of mRNA COVID-19 vaccine-induced myocarditis remains unknown. It has been suggested that excessive innate immune activation by both lipid nanoparticle and RNA components of COVID-19 vaccines can cause myocarditis [24,25]. Endosomal toll-like receptor (TLR) TLR3, TLR7, and TLR8 in immune cells and RIG-I and MDA5 in nonimmune cells act as a natural defense against foreign RNA but can crossreact with in vitro transcribed (IVT) RNA [26].…”
Section: Discussionmentioning
confidence: 99%
“…Endosomal toll-like receptor (TLR) TLR3, TLR7, and TLR8 in immune cells and RIG-I and MDA5 in nonimmune cells act as a natural defense against foreign RNA but can crossreact with in vitro transcribed (IVT) RNA [26]. The activation of these receptors triggers an inflammatory cascade, assembly of inflammasome platform production of type I interferons, and nuclear translocation of NK-kB [24,25,27]. Inflammasomes are large multiproteins that are responsive to pathogen-and stress-associated cellular insults.…”
Section: Discussionmentioning
confidence: 99%
“… 123 Importantly, these complications are now well documented, and can be recognized and treated early to avoid long‐term complications. 126 , 127 , 128 , 129 …”
Section: Recent Insights Into Dynamics Of Immune Memory To ...mentioning
confidence: 99%
“…Myocarditis following mRNA vaccination is more prominent in young men with 1.7 in 100,000 affected 123 . Importantly, these complications are now well documented, and can be recognized and treated early to avoid long‐term complications 126–129 …”
Section: Recent Insights Into Dynamics Of Immune Memory To Covid‐19 V...mentioning
confidence: 99%
“…Studies from the USA show that the risk of myocarditis after receiving mRNA-based COVID-19 vaccines is increased across all age and sex groups. Epidemiological studies reported an incidence of 20–30 per million patients, and the risk is highest after the second vaccination dose in adolescent males 2 3. The Centers for Disease Control and Prevention (CDC) recommends that COVID-19 primary series vaccines should be given to everyone aged 6 months and older with COVID-19 boosters for everyone 5 years and older 4.…”
Section: Introductionmentioning
confidence: 99%